Dynamic characteristics of novel energy dissipation systems with damped outriggers. (1st September 2015) - Tan, P.; Fang, C.J.; Chang, C.M.; Spencer, B.F.; Zhou, F.L.
Highlights: Complex stiffness of multiple damped outriggers is modeled and derived. Dynamic characteristic is obtained by combining with dynamic stiffness matrix. A finite element model verified the correctness of the proposed method. The ratio of core-to-column stiffness influences the modal damping significantly. Optimal damping should also match with mode order and outrigger position. Abstract: This study proposes complex rotational stiffness for modeling multiple damped outriggers in a tall building. The complex rotational stiffness considers interaction between peripheral columns and the dampers in damped outriggers. By combining the complex rotational stiffness into a dynamic stiffness matrix, the dynamic characteristics of a building with multiple outriggers can be derived in accordance to the Benoulli–Euler beam theory. These dynamic characteristics subsequently provide a guideline for designing outriggers in a building. In this study, the proposed method is verified in comparison with a finite element model. An in-depth parametric study is then conducted by the proposed method to evaluate a building with outriggers with respect to the stiffness ratio of the core to perimeter columns, position of damped outriggers, and damping coefficient of linearly viscous dampers. The investigation shows that the modal damping is significantly influenced by the ratio of core-to-column stiffness, as well as is more sensitive to the damping coefficient of dampers than to the position of damped outriggers. All of the results obtained are non-dimensional and convenient for analysis and applications of designing damped outrigger systems.